Harvey v Beveridge: Common Intention Constructive Trusts in New Zealand? - Bennett, Mark (Victoria University of Wellington Law Review, 2015)
This article discusses the reasoning of the High Court and Court of Appeal in Harvey v Beveridge in respect of the existence of "common intention constructive trusts" in New Zealand law. It analyses the development of constructive trusts doctrine in New Zealand, and argues that a different approach was taken to the application of this doctrine in relationship property disputes compared with the equivalent English doctrine. This difference was not recognised in Harvey v Beveridge, and it is argued that an adequate understanding of this difference requires us to grapple with the underlying foundations of the New Zealand law, which were left open during the Court of Appeal's development of the doctrine.